Applied normal load and printing layer thickness relationship on the tribological properties of novel 3D-printed PLA-PCU polymer blend - Abdollah, Mohd Fadzli bin; Ramli, Faiz Redza; Shaharuddin, Shanahs; Amiruddin, Hilmi; Kamis, Shahira Liza (Malaysian Tribology Society, 2023)
This study aims to investigate the tribological properties of a new additively manufactured polymer blend made of polycarbonate-urethane (PCU) and poly(lactic acid) (PLA) under lubricated conditions. A ball-on-disc tribometer was utilised to conduct tribological testing. The findings found that the PLA-PCU polymer blend has a lower elastic modulus and hardness than pure PLA. However, there is no substantial difference in tribological properties between the two materials. Regardless of polymer blend composition, the coefficient of friction (COF) and wear rate of 3D-printed materials decrease with increasing printing layer thickness and applied normal load. The wear mechanisms are dominated by plastic deformation. As the applied normal load increases, the deformation regime transitions from abrasive wear and surface microcracks to compaction and layer detachment.